Emission Reduction Scores and Market Behaviour: Analysing Stock Synchronicity in India - Potharla, Srikanth; Turubilli, Surya Kumari (The Indonesian Journal of Accounting Research, 2024)
This study investigates the relationship between Emission Reduction Scores (ERS) and stock price synchronicity among 151 listed Indian companies from 2011 to 2022. Our findings demonstrate a significant negative association between ERS and stock price synchronicity, indicating that companies with higher emission reduction practices exhibit less synchronized stock prices. This reduced synchronicity is attributed to the greater incorporation of firm-specific information into stock valuations, which enhances resilience against systematic market risks. This analysis provides valuable insights for investors, regulators, and academics, highlighting the critical role of transparent environmental performance disclosures in improving market efficiency. These findings support improved portfolio diversification and risk management strategies and offer a holistic understanding of how environmental sustainability initiatives impact economic prosperity.